2023
DOI: 10.15408/etk.v22i1.30605
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Halal Lifestyle on Career Women in Indonesia

Abstract: The halal industry is experiencing rapid development, one of which is the increasing demand for halal products. Studying the halal lifestyle for career women is interesting because of the growing development of Muslim fashion and halal cosmetics. The originality of this research lies in a comprehensive study of the halal lifestyle in career women. This study aimed to determine the effect of religiosity, knowledge, awareness, and social environment on the halal lifestyle of career women in Jakarta Province. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A survey conducted by Pricewaterhouse Coopers International (PwC) in 2023 showed that the level of job satisfaction among employees in Indonesia is quite high, reaching 75%. This figure is above the average level of job satisfaction among employees in the Asia Pacific region, which is 57% (Salsabila, 2023). Based on the phenomenon and facts above, with the increasing job satisfaction of employees, all company activities can run smoothly.…”
Section: Introductionmentioning
confidence: 77%
“…A survey conducted by Pricewaterhouse Coopers International (PwC) in 2023 showed that the level of job satisfaction among employees in Indonesia is quite high, reaching 75%. This figure is above the average level of job satisfaction among employees in the Asia Pacific region, which is 57% (Salsabila, 2023). Based on the phenomenon and facts above, with the increasing job satisfaction of employees, all company activities can run smoothly.…”
Section: Introductionmentioning
confidence: 77%
“…The Indonesian government, through BPJPH, remains committed to promoting the halal industry and ensuring consumer access to halal products compliant with Islamic law, thus catalyzing economic growth. (Salsabila & Nur, 2023) Traditionally, Muslim-majority countries, particularly those in the Middle East and Southeast Asia, such as Malaysia, are synonymous with the halal industry. The Annual Report on the World Islamic Economy underscores that a significant portion of the Islamic economic sector resides in developing countries, with the top 10 Islamic economic powers comprising predominantly developing nations.…”
Section: Discussionmentioning
confidence: 99%